1978
DOI: 10.1126/science.675256
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone of the Tsetse Fly: Isolation, Identification, and Synthesis of Contact Aphrodisiacs

Abstract: Sex pheromones isolated from the cuticle of the female tsetse fly, Glossina morsitans morsitans Westwood, release mating behavior in the male fly at ultrashort range or upon contact with baited decoys. Three active components were identified as 15,19-dimethylheptatriacontane, 17,21-dimethylheptatriacontane, and 15,19,23-trimethylheptatriacontane. Chemical and biological comparisons show that the natural and synthetic compounds are identical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 12 publications
1
74
0
1
Order By: Relevance
“…Cuticular hydrocarbons long have been proposed to play a role in courting behavior and mating (Carlson et al 1978;Markow and Toolson 1990). We observed a significant upregulation of desaturase-2 (desat2) in D. mojavensis females following mating.…”
Section: Discussionmentioning
confidence: 73%
“…Cuticular hydrocarbons long have been proposed to play a role in courting behavior and mating (Carlson et al 1978;Markow and Toolson 1990). We observed a significant upregulation of desaturase-2 (desat2) in D. mojavensis females following mating.…”
Section: Discussionmentioning
confidence: 73%
“…Rogoff et al (1964) reported that benzene extracts of female Musca domestica (L.) elicited both attraction and excitation of mating behavior patterns in males. Carlson et al (1971) have found Z-9-tricosene as sex attractant for house fly; similarly, the versatile role of hydrocarbons in different insects such as stable fly (Muhammed et al 1975), little house fly (Uebel et al 1977), horn fly (Macklay 1977), tsetse fly (Carlson et al 1978;Huyton et al 1980;Carlson and Schlein 1991), and fruit fly (Oguma et al 1992a, b) has been elucidated. Moore and Fisher (1969) have reported that a metabolite released into the water by Ae.…”
Section: Introductionmentioning
confidence: 97%
“…The two pheromones, the non-volatile MSP and the volatile ASP, may function in a synergistic manner to enable the male to reach the female's gonopore. Perhaps the volatile sex pheromone enhances the effect of the contact sex pheromone just as vision, tactile stimuli or interactive behavior patterns enhance the contact sex pheromone perception in some insects (Carlson et al, 1978;Langley et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been conducted on the identification of the cuticular contact sex pheromones and their receptors in the African tsetse flies because of their importance as vectors of African sleeping sickness. Langley et al (1975) first described the cuticular contact sex pheromone of Glossina (morsitans) morsitans as 15, 19, 23-trimethyl-heptatriacontane; later, Carlson et al (1978) isolated, identified and synthesized the compound along with non-stimulatory components of the pheromone. Carlson et al (1978), Huyton et al (1980), Langley et al (1982) and Langley and Hall (1984) also noted that visual and tactile stimuli are important in the mating behavior of tsetse flies.…”
Section: Discussionmentioning
confidence: 99%